Role of VEGFR2 in Mediating Endoplasmic Reticulum Stress Under Glucose Deprivation and Determining Cell Death, Oxidative Stress, and Inflammatory Factor Expression - Xu, Bohan; Zhou, Linbin; Chen, Qishan; Zhang, Jianing; Huang, Lijuan; Wang, Shasha; Ye, Zhimin; Ren, Xiangrong; Cai, Yu; Jensen, Lasse Dahl; Chen, Weirong; Li, Xuri; et al. (Frontiers in Cell and Developmental Biology, 2021)
Retinal pigment epithelium (RPE), a postmitotic monolayer located between the neuroretina and choroid, supports the retina and is closely associated with vision loss diseases such as age-related macular degeneration (AMD) upon dysfunction. Although environmental stresses are known to play critical roles in AMD pathogenesis and the roles of other stresses have been well investigated, glucose deprivation, which can arise from choriocapillary flow voids, has yet to be fully explored. In this study, we examined the involvement of VEGFR2 in glucose deprivation-mediated cell death and the underlying mechanisms. We found that VEGFR2 levels are a determinant for RPE cell death, a critical factor for dry AMD, under glucose deprivation. RNA sequencing analysis showed that upon VEGFR2 knockdown under glucose starvation, endoplasmic reticulum (ER) stress and unfolded protein response (UPR) are reduced. Consistently, VEGFR2 overexpression increased ER stress under the same condition. Although VEGFR2 was less expressed compared to EGFR1 and c-Met in RPE cells, it could elicit a higher level of ER stress induced by glucose starvation. Finally, downregulated VEGFR2 attenuated the oxidative stress and inflammatory factor expression, two downstream targets of ER stress. Our study, for the first time, has demonstrated a novel role of VEGFR2 in RPE cells under glucose deprivation, thus providing valuable insights into the mechanisms of AMD pathogenesis and suggesting that VEGFR2 might be a potential therapeutic target for AMD prevention, which may impede its progression.ER stress